(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
University of Vienna professor of sociology Emma Dowling presents a cogent exploration of how austerity measures and the privatisation of social welfare and health services in the UK have resulted in a lack of suitable options for those in need. She notes that women are more likely than men to lose income as a result of caring for children; that people of colour are disproportionately harmed by government cuts in spending on social care; and that migrants make up a significant proportion of care workers and are often paid below the minimum wage. Since the 1990s, Dowling explains, local authorities have been encouraged to contract out care services to private providers, supposedly with the goal of offering more personalised care. Corporate takeovers, however, have resulted in a focus on shareholder profits rather than effective provision. Her proposed solutions include reducing privatisation, “publicly funding new and innovative models for care,” and improving working conditions for health-care employees. Blending sociological research and in-depth interviews, Dowling touches on many issues faced by both the recipients of care and the providers of care in the UK and the US, presenting a lucid and alarming picture of how political decisions have place obstacles in the way of progress towards better care. Readers on both sides of the Atlantic will appreciate this passionate and persuasive call for reform.